A compact sub-Hertz local field potential amplifier for implantable biomedical devices. (October 2022) - Dwivedi, Shashank; Gogoi, Anup K.
Abstract: Local field potentials (LFPs) are the ensemble of low frequency neural signals recorded invasively via microelectrodes implanted into brain tissues. The LFP signals acquired by micro-electrodes are very small in amplitude, typically in the range of 1 μ V to 0.5 mV, depending on the distance from the electrode and on the size of a cell and contain the signal energy below 1 Hz. These weak signals are required to be amplified by an analog front-end amplifier. In this paper, the design methodology of a local field potential amplifier for an implantable neural recording system is presented. The LFP amplifier is implemented through a low power, low noise front-end instrumentation amplifier. In order to suppress large electrode-induced DC offset voltages, a modified pseudo-resistor is employed in the amplifier's feedback. The enlarged resistance offered by the pseudo resistor realizes a high-pass cut-off frequency which is well suited for capturing the neural signals occurring in the sub-Hertz frequency range. As a case study, the instrumentation amplifier featuring modified pseudo resistor configured for LFP recording applications is fabricated in a standard 0 . 18 μ m CMOS process technology. The measurement results show the proposed LFP amplifier has a low-pass corner frequency of 300 Hz and achieves a high-pass corner frequency of 0.009 Hz with a maximum gain of 37 dB. The LFP circuit fully integrated on-chip occupies an active area of 0.056 mm 2 and a power consumption of 1.8 μ W from a 1.5-V supply.